Evaluación de riesgo ergonómico en el área de faenamiento y su incidencia en la salud de los trabajadores en el camal municipal del cantón Mejía. - Suntaxi Caizatoa, Jorge Daniel (2018)
This research project is carried out for Evaluation of ergonomic risks and their impact on the workers’ health, this is an initial study, will reduce the rate of occupational diseases and improve working conditions in each of the areas those where have been identified ergonomic risks in the municipal slaughterhouse in the Mejia Canton Pichincha Province, where the main activity is cattle slaughter services to the major and minor. This research was based on an ergonomic evaluation using the Owas method, since it is the traditional and basic method to do a study related to ergonomics, which identifies the most relevant risks of the worker, through an analysis of the different working postures of the body. Such as: arms, legs and back, and the relative frequency in the case of constant or repetitive movements into people who work at the slaughterhouse. The research out the evaluation of the ergonomic risks to which the workers of the municipal slaughterhouse are exposed, with all the information and measurements obtained giving them some prevention and protection measures such as: active breaks during the working day, staff rotation as well as talks and training regarding occupational health and safety. Key words: Relevant, evaluation, risks, ergonomics, Owas method, prevention, occupational safety and health, active breaks.